Pajanan Pestisida Sebagai Faktor Risiko Kejadian Berat Badan Lahir Rendah (BBLR) : Sebuah Kajian Sistematik - Amanda Luky Ernawati; Tri Joko; Suhartono (Universitas Widya Gama Mahakam Samarinda, 2021)
Background: Low birth weight (LBW) is one of the causes of infants death. One of the factors that is proven to be associated with LBW incidence is pesticide exposure to pregnant women. The high number of female farmers in the agricultural sector will increase the risk of pesticide exposure in pregnant women. Objectives: This study aims to describe how pesticide exposure can be a risk factor for the incidence of LBW. Research method: This study is a systematic study that used meta-synthesis aggregation approach. The search for articles focused on articles that examined the risk factors for pesticide exposure on the incidence of LBW in pregnant women which was conducted on the online databases of Science Direct, Scopus, PubMed, Springer, Google Scholar, and Garuda Portal. The criteria for the articles used were national observational journals indexed at least 4 and indexed international journals published in 2010-2020. Result: There were 9 articles that match to the criteria and research topic. Factors that were proven to increase the risk of LBW incidence in pregnant women were agricultural activities related to pesticide, participation in agricultural activities, completeness of PPE, storage of pesticide, duration of exposure to pesticide, frequency of exposure to pesticide, amount of pesticide mixture, and types of pesticide used. Conclusion: Pesticide exposure to pregnant women causes the accumulation of pesticide residues in the body, thus reducing the formation of thyroid hormones and IGF-1 which can cause LBW.